Virtual screening, molecular dynamics and binding energy-MM-PBSA studies of natural compounds to identify potential EcR inhibitors against Bemisia tabaci Gennadius - Harmilan Kaur Mangat; Manisha Rani; Rajesh Kumar Pathak; Inderjit Singh Yadav; Divya Utreja; Pardeep Kumar Chhuneja; Parveen Chhuneja (PLoS ONE, 2022)
Whitefly (Bemisia tabaci Gennadius) is a hemipteran phyto polyphagous sucking insect pest which is an important pest of cotton that causes economic losses to the crop by reducing its yield and quality. Ecdysteroids such as 20-hydroxy ecdysone (20-E), play a significant role in larval moulting, development, and reproduction in pterygota insects. Receptor of 20-E, that is Ecdysone Receptor (BtEcR) of Bemisia tabaci has been targeted to prevent fundamental developmental processes. To identify potent inhibitors of BtEcr, 98,072 natural compounds were retrieved from ZINC database. A structure-based virtual screening of these compounds was performed for evaluating their binding affinity to BtEcR, and top two compounds (ZINC08952607 and ZINC04264850) selected based on lowest binding energy. Molecular dynamics simulation (MDS) study was performed for analyzing the dynamics and stability of BtEcR and top-scoring ligand-BtEcR complexes at 50 ns. Besides, g_mmpbsa tool was also used to calculate and analyse the binding free energy of BtEcR-ligand complexes. Compounds ZINC08952607 and ZINC04264850 had shown a binding free energy of −170.156 kJ mol-1 and −200.349 kJ mol-1 in complex with BtEcR respectively. Thus, these compounds can be utilized as lead for the development of environmentally safe insecticides against the whitefly.